K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

15 tháng 11 2018

456 - 4(x+52) = 185

4(x+52)=271

x+52=67,75

x=15,75

=.= hok tốt!!

10 tháng 12 2021

Answer:

Bài 3:

\(334-\left(-75\right)+[\left(-175\right)-34]\)

\(=334+75-175-34\)

\(=\left(334-34\right)+\left(75-175\right)\)

\(=300+\left(-100\right)\)

\(=200\)

\(68-\left(-45\right)-[368-\left(-145\right)]\)

\(=68+45-[368+145]\)

\(=\left(68-368\right)+\left(45-145\right)\)

\(=\left(-300\right)+\left(-100\right)\)

\(=-400\)

Bài 4:

\(-17-\left(x-5\right)=-52\)

\(\Rightarrow x-5=-17-\left(-52\right)\)

\(\Rightarrow x-5=35\)

\(\Rightarrow x=40\)

\(3\left(7-x\right)+\left(-12\right)=-75\)

\(\Rightarrow3\left(7-x\right)=-75-\left(-12\right)\)

\(\Rightarrow3\left(7-x\right)=-63\)

\(\Rightarrow7-x=-21\)

\(\Rightarrow x=28\)

19 tháng 12 2021

khó quá ??????????????????????????????????

19 tháng 12 2021

a) (-2) . ( x+7 ) + (-5) = 7 

<=>(-2).(x+7)=7+5

<=>x+7=12:(-2)

<=>x+7=-6

<=>x=(-6)-7

<=>x=-13

Vậy x=-13

b)(x+4) : (-7) = 14

<=>x+4=14 x (-7)

<=>x+4=-98

<=>x=-98-4

<=>x=-102

Vậy x= -102

c) 72 : ( x+5) - 4 = -12 

<=>72:(x+5)=(-12)+4

<=>x+5=72:(-8)

<=>x+5=-9

<=>x=-9-5

<=>x=-14

Vậy x= -14

d) (x+3) : (-6 ) + 12 = 8 

<=>(x+3) :(-6)=8-12

<=>x+3=(-4)x(-6)

<=>x+3=24

<=>x=24-3

<=>x=21

Vậy x= 21 

18 tháng 12 2015

x+22-14+52=x+52-14=x+74-14=x+60
TICK NHÁ!!!

3 tháng 8 2016

(2+x)+(4+x)+...+(52+x)=780

=>(x+x+...+x)+(2+4+...+52)=780

=>26x+702=780

=>26x=78

=>x=3

3 tháng 8 2016

=>(2+4+...+52)+(x+x+...+x)=780        (26 số hạng x)

=>(52+2).26/2+26x=780

=>702+26x=780

=>26x=780-702

=>26x=78

=>x=78:26

=>x=3

23 tháng 8 2018

đáp án là:2004456

23 tháng 8 2018

2005 x 456 + 2004 x 544 = 2004456

7 tháng 7 2019

25 x 34 + 65 x 75 - 35 x 86 + 65 x 45

= 5 x 17 x 10 + 65 x (75 + 45) - 7 x 43 x 10

= 85 x 10 + 780 x 10 - 301 x 10

= 10 x (85 + 780 - 301)

= 10 x 564

= 5640

12000 nha bẹn iu

26 tháng 1 2021

a) 2x - ( 40 - 52 ) = x + 12

       2x - 40 + 52 = x + 12

                        x = 0

b) 40 - x =-12 + 3x

         4x = 52

           x = 13

20 tháng 5 2021

a) 2x - ( 40 - 52 ) = x + 12

       2x - 40 + 52 = x + 12

                        x = 0

b) 40 - x =-12 + 3x

         4x = 52

           x = 13